2013
DOI: 10.1590/0037-8682-0012-2013
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of antimicrobial combinations against multidrug-resistant Pseudomonas aeruginosa

Abstract: Introduction: Pseudomonas aeruginosa isolates related to nosocomial infections are often resistant to multiple antibacterial agents. In this study, antimicrobial combinations were evaluated to detect in vitro synergy against clinical isolates of P. aeruginosa. Methods: Four clinical P. aeruginosa isolates were selected at random among other isolates from inpatients treated at the public University hospital in Ribeirão Preto, SP, Brazil. Two isolates were susceptible to imipenem (IPM-S) and several other antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
(18 reference statements)
0
10
0
1
Order By: Relevance
“…We tested combinations of Ag with different transition metals (Cu, Co, Zn, Ni and Cd) via a checkerboard assay, a widely used methodology to test synergistic effects between antimicrobial agents 38, 4951 . The inhibitory effect of the different transition metal combinations with silver against E. coli is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We tested combinations of Ag with different transition metals (Cu, Co, Zn, Ni and Cd) via a checkerboard assay, a widely used methodology to test synergistic effects between antimicrobial agents 38, 4951 . The inhibitory effect of the different transition metal combinations with silver against E. coli is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using checkerboards/FICI, aminoglycosides, piperacillin-tazobactam, ceftazidime, cefepime, and ciprofloxacin were also synergistic with fosfomycin against CR P. aeruginosa strains (151). In one more study, in which the resistance profile of P. aeruginosa was not reported, synergy (using FICI) between fosfomycin and aminoglycosides was observed for 60% to 80% of tested strains, with amikacin and isepamicin demonstrating the higher synergy rates (27).…”
Section: Newer Studiesmentioning
confidence: 98%
“…Several in vitro SCTK and checkerboard studies have shown synergy for piperacillintobramycin against P. aeruginosa (35)(36)(37)(38)(39). A small number of dynamic HFIM and in vivo infection model studies conducted using other ␤-lactam plus aminoglycoside combinations have also demonstrated beneficial effects against P. aeruginosa (40)(41)(42)(43).…”
Section: Figmentioning
confidence: 99%